Pregnancy toxaemia of ewes. A literature review - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ), N.; BROZOS (Χ. ΜΠΡΟΖΟΣ), C.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ), G. C.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Pregnancy toxaemia is a metabolic disorder of ewes, occurring at the final stage of pregnancy. In this review article, the literature on the aetiology and the pathogenesis of the disease is reviewed, the clinical, laboratory and postmortem findings are described, the diagnosis is presented and the control of the disease is discussed.